Glorifying Neighbors and Guests from a Hadith Perspective and its Relation to the Level of Faith - Andaluzi, Fahmi; Fatah, Abdul (TATHO: International Journal of Islamic Thought and Sciences, 2024)
Dynamic social patterns will undergo changes in various community systems including the concept of being a neighbor and guest which is a major part of daily activities. These developments and changes will experience stagnation and even conflict between individuals or community groups if they are not accompanied by good values as a basic footing in socializing. This paper seeks to explore the Hadith's view on the noble attitude towards neighbors and guests and its relationship to the level of faith. This research fully uses library research by applying the descriptive-analytical method, namely by presenting the related traditions and analyzing their relation to the level of faith.The results of this study show that honoring neighbors and guests has a strong urgency in the view of the hadith. Good behavior towards neighbors and guests is important to be applied in social life. A good attitude towards neighbors is not only limited to the rules applied in social ethics, but has a connection with the faith of a Muslim where the attitude towards neighbors and guests is one of the strong indicators of the level of faith of a Muslim. From the analysis of the traditions studied, it can be concluded that honoring neighbors and guests is highly considered in Islam, these noble morals are not only limited to commands but as a benchmark for the level of perfection of one's faith.